Analysis of the Impact of Electronic Money Usage as a Payment Tool on Economic Growth - ,, Agustina; Rustam, Rinaldi (Dinasti Publisher, 2025)
This research is conducted for the journal with the aim of analyzing the effects of electronic payment systems based on credit cards, debit cards, and electronic money, as well as macroeconomic variables such as the money supply (M1), price levels, and exchange rates on real gross domestic product (GDP) as a proxy for economic growth. The estimations in this journal use the Vector Error Correction Model (VECM) with monthly time series data for the period from 2012 to 2023. The results indicate that transactions using debit cards and electronic money have a significant positive effect on economic growth in Indonesia in the long term.